Analisis Dampak Transformasi Pendidikan Pesantren Terhadap Penanaman Jiwa Keikhlasan Santri di Pondok Pesantren - Ahmad Suradi (Institut Agama Islam Negeri (IAIN) Tulungagung, 2018)
This article aims to examine the impact of the transformation of pesantren education on the cultivation of santri's sincere values ​​in pesantren. The method used in the discussion of this article is descriptive qualitative method, which comes from interviews and observations in the field. This article discusses that the impact of the transformation of pesantren education today, not only changed the socio-cultural base and knowledge of santri alone, but also influenced the values ​​of the spirit of santri sincere in boarding schools. Therefore, major changes made by kyai to pesantren institutions today have an impact on the sincere behavior of santri in everyday life. In terms of planting the values ​​of the soul of sincerity in the boarding school is expected to open and flexible to the development of the world, but still provides a filter for its basic value is not fade (Islamic teachings). Because, as opposed to the current, as hard as it retains, in the end it will sooner or later be carried away as well. This process is a natural law that can not be dammed, but it needs to be addressed the present situation wisely, so as not to conflict with the basic Islamic teachings. It is not an alternative choice that crossed the way, but is an accumulation of the values ​​of life experienced by pesantren throughout its history, leaving no soul of sincerity or traditions.